A contribuição do homem simples na construção da esfera pública: os trabalhadores rurais de Baturité Ceará - Sônia Pereira (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Analyses the participative experience of the ordinary man the rural landless worker, lease-holder or tenant farmer in public spaces like municipal councils, associations of small producers and the Rural Workers Trade Union, in Baturité, a municipality of 30,000 inhabitants in the State of Ceará. The research took as its starting point a basic question: how does the ordinary man experience politics today? Understanding politics as transgression, dispute or the changing of positions, achieved by means of discussion and demands, and by examining the possibility of constructing a public sphere, the research followed systematically the participative experiences of two rural communities, which are characterised as State offers and as civil society conquests. The participative dynamic is established by involving conflicting movements which at times are characterised as democratic and transparent relations between State and civil society and, at others, as traditional relations based on authoritarianism and cordiality, salient features of Brazilian political culture. Although the material conquests of the associative experiences are limited, gradual approximations to a style of democratic being are experienced and these, in turn, signal the production of a legacy: the quest for citizenship and the awareness of rights.